Pengaruh Kualitas Pelayanan dan Harga terhadap Keputusan Pembelian pada PT Lautan Berlian Utama Motor Jakarta Barat - Mulyadi, Mulyadi; Pasaribu, Veta Lidya Delimah (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2024)
The purpose of this research is to find out how much influence Service Quality has on purchasing decisions at PT Lautan Berlian Utama Motor West Jakarta Branch, to find out how much influence price has on purchasing decisions at PT Lautan Berlian Utama Motor West Jakarta Branch and to find out how much influence Service quality and price influence purchasing decisions at PT Lautan Berlian Utama Motor West Jakarta Branch simultaneously. The research method in this research is a quantitative method. The population in this study is based on consumer complaints in 2022, PT Lautan Berlian Utama Motor West Jakarta Branch, totaling 204 consumers. The sampling technique for this research is simple random sampling, determining the sample size using the Slovin formula with a difficulty level of 10%, so a sample of 67 buyer respondents was obtained. The data used is through observation techniques, questionnaires and literature. The analytical methods used in this research are validity test, reliability test, normality test, multicollinearity test, heteroscedasticity test, simple linear regression test, multiple linear regression test, determination test and significance test (t test and f test). The research results obtained partial positive service quality results on purchasing decisions, this can be seen from the t test with a t value of 10.015 > t table 1.669 with a significance value of 0.000, this value is smaller than 0.05 (0.000 < 0.05). partially price has a positive effect on purchasing decisions, this can be seen from the t test with a value of tcount 7.575 > ttable 1.669 with a significance level of 0.000, this value is greater than 0.05 (0.000 < 0.05) and simultaneously price and promotion have a positive effect and significant for purchasing decisions, this can be seen from the results of the f test with fcount 61.191 and ftable 3.140 with a significance of 0.000 < 0.05. Thus, it can be interpreted that service quality and price simultaneously have a significant influence on purchasing decisions.